In vivo and In vitro effect of a nutrient mixture on human hepatocarcinoma cell line SK-HEP-1 - Roomi, M.W.; Roomi, N.W.; Kalinovsky, T.; Niedzwiecki, A.; Rath, M. (Experimental Oncology, 2010)
Long-term survival of patients with hepatocellular carcinoma (HCC), a common cancer worldwide, remains poor, due to metastasis and recurrence. Aim: To investigate the effect of a novel nutrient mixture (NM) containing ascorbic acid, lysine, proline, and green tea extract on human HCC cell line Sk-Hep-1 In vivo and In vitro. Methods: After one week of isolation, 5–6 week old male athymic nude mice were inoculated with 3 x 106 SK-Hep-1 cells subcutaneously and randomly divided into two groups; group A was fed a regular diet and group B a regular diet supplemented with 0.5% NM. Four weeks later, the mice were sacrificed and their tumors were excised, weighed and processed for histology. We also tested the effect of NM In vitro on SK-Hep-1 cells, measuring cell proliferation by MTT assay, invasion through Matrigel, apoptosis by green caspase detection kit, MMP secretion by zymography, and morphology by H&E staining. Results: NM inhibited tumor weight and burden of SK-Hep-1 xenografts by 42% and 33% respectively. In vitro, NM exhibited 33% toxicity over the control at 500 and 1000 μg/ml concentration. Zymography demonstrated MMP-2 and MMP-9 secretion which was inhibited by NM in a dose dependent fashion, with virtual total inhibition at 1000 μg/ml. Invasion through Matrigel was inhibited at 100, 500 and 1000 μg/ml by 53%, 83% and 100% respectively. NM induced slight apoptosis at 100 μg/ml, and profound apoptosis at 500 μg/ml and 1000 μg/ml concentration. Conclusions: These results suggest that NM has therapeutic potential in treatment of HCC.